2015
DOI: 10.4283/jmag.2015.20.4.336
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Magnetic Properties of MnBi Alloy and its Hybridization with NdFeB

Abstract: MnBi alloys were fabricated by arc melting and annealing at 573 K. The heat treatment enhanced the content of the low-temperature phase (LTP) of MnBi up to 83 wt%. The Bi-excess assisted LTP MnBi alloys were used in the hybridization with the Nd-Fe-B commercial Magnequench ribbons to form the hybrid magnets (100-x)NdFeB/xMnBi, x = 20, 30, 40, 50, and 80 wt%. The as-milled powder mixtures of Nd-Fe-B and MnBi were aligned in a magnetic field of 18 kOe and warm-compacted to anisotropic and dense bulk magnets at 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…It revealed that the realization of this balance is, in the case of MnBi bulk magnets, crucially required and contributes an important role in enhancing the energy product (BH)max of MnBi bulk magnets. It has been proved that to have this balance, the route of producing MnBi bulk magnets should be carefully controlled to i) prepare alloys with the spontaneous magnetization Ms higher 8 kG; ii) grind alloys into powders owning the relation iHc(in kOe) > Mr(in kG); iii) warrantee the high alignment degree  of the bulk magnet greater 50; iv) use the compaction pressure Popt around 1700 psi to reach the magnet mass density  around 8.5 g/cm 3 . These listed values are the guide ones for controlling the route of producing high-performance MnBi bulk magnets with (BH)max towards the theoretical limit.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It revealed that the realization of this balance is, in the case of MnBi bulk magnets, crucially required and contributes an important role in enhancing the energy product (BH)max of MnBi bulk magnets. It has been proved that to have this balance, the route of producing MnBi bulk magnets should be carefully controlled to i) prepare alloys with the spontaneous magnetization Ms higher 8 kG; ii) grind alloys into powders owning the relation iHc(in kOe) > Mr(in kG); iii) warrantee the high alignment degree  of the bulk magnet greater 50; iv) use the compaction pressure Popt around 1700 psi to reach the magnet mass density  around 8.5 g/cm 3 . These listed values are the guide ones for controlling the route of producing high-performance MnBi bulk magnets with (BH)max towards the theoretical limit.…”
Section: Resultsmentioning
confidence: 99%
“…All the ball mill were done by 6 mm hard steel balls with the weighing ratio of balls:powders of 10:1. The composition phases of alloys and ball-milling powders were carried out by using D8 advance Brucker X-ray diffractometer (XRD) with Cu-K radiation with the scattering angle 2 scan in the range from 20 to 80 degrees by the scanning step of 0.05° for 2 s. The phase composition were analyzed by means of Rietveld refinement of XRD patterns for all the obtained diffraction peaks by using the Crystal Impact -Software for Chemists and Material Scientists and, in some cases, by the method of the instant determination of MnBi LTP content presented in the previous work [3]. The morphology of powders was studied by using the Field Emission Scanning Electron Microscopy FESEM Hitachi S-4800.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the difficulties in synthesizing highperformance LTP-MnBi is caused by the dissociation of Mn because of the peritectic interaction between Mn and Bi as seen in the Mn-Bi phase diagram. The peritectic reaction results in the interruption of LTP-MnBi formation, and there will always be an excess of Bi upon this reaction [8]. There is an attempt to separate the excess Bi using a magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…The essential for getting different magnetic performances is the peritectic reaction during MnBi synthesis [6]. The MnBi can be prepared by various approaches, such as arc-melting [7], melt-spinning [8], chemical reaction [9], and sintering [4]. The sintering technique employs a diffusion process that can synthesize high-purity LTP-MnBi [10].…”
Section: Introductionmentioning
confidence: 99%